Attention to words in different modalities: four-channel presentation with physical and semantic selection. - Martin, M (1980)
Theoretical controversy surrounds the issue of whether central processing capacity is unitary and general or whether different types of processing capacity may be distinguished. Three bisensory experiments investigated the selection of words by physical and semantic attributes. It was found that recall was superior following bimodal (auditory and visual) rather than unimodal (auditory or visual) presentation. Furthermore, the difference between bimodal and unimodal recall was greater when the words were physically selected than when they were semantically selected. The results provide evidence that the availability of different types of processing capacity is dependent upon the mode of presentation of material and its required type of analysis. © 1980.